A Review on efficient thermal management of air- and liquid-cooled data centers: From chip to the cooling system - Habibi Khalaj, Ali; Halgamuge, Saman K. (Applied energy, 2017)
•Discussed thermal challenges of data centers.•Reviewed thermal management techniques of data centers from chip to the cooling system.•Compered various modelling and optimization methods of air-cooled data centers.•Compered technical characteristics of various direct and indirect liquid-cooled data centers.•Reviewed thermal performance of various air- and water-side economizers. The growing global demand for services offered by data centers (DCs) has increased their total power consumption and carbon emissions. Recent figures revealed that DCs account for around 2% of total US electrical power consumption, approximately 40% of which is for powering their cooling systems. A high portion of energy spent on cooling is typically due to the inherent inefficiency of the heat removal process existing in multi-level from microchip to the cooling infrastructure level. Depending on the type of cooling system, air-cooled or liquid-cooled, this inefficiency can be significantly improved upon by utilizing various thermal management and efficiency enhancement techniques at each level. This paper reviews the state-of-the-art of multi-level thermal management techniques for both air- and liquid-cooled DCs. The main focus is on the sources of inefficiencies and the improvement methods with their configuration features and performances at each level. For the air-cooled DCs, various advanced methods for the chip, server, rack, plenum and room levels have been reviewed. Recent advances in thermal modelling of air-cooled DCs and their energy optimization methods have also been broadly reviewed. Furthermore, the performance of various methods such as pool boiling, jet impingement, and spray cooling for direct liquid-cooled DCs and single-phase, two-phase and heat pipe cooling for indirect liquid-cooled DCs have been compared. Finally, free cooling as an energy efficient method in reducing total power consumption of DCs’ cooling system has been reviewed in this paper. The advancements in two main types of free cooling methods, air-side and water-side economizers, are discussed and their performance characteristics are compared.